H03 Rate of progression is associated with age of disease onset for all HD. (29th August 2012) - Paulsen, JS; Long, JD; ,
Abstract : Background: Understanding the rate of progression in HD is a key component for the design of clinical trials. Previous research has shown a significant positive relationship between the rate of disease progression and the length of the CAG repeat length and/or the age of disease onset. Much of this research has been criticised as driven by outliers and/or accounted for by the most extreme cases. For instance, CAG lengths greater than 60 often manifest as juvenile onset and demonstrate a more rapid decline. Aims: A large collaborative dataset from the Huntington Study Group was analysed to examine whether the relationship between progression rate and onset age was consistent regardless of outliers. Methods: 4607 participants were included in the analyses although complete data were available for 2960. Years of longitudinal study varied from 1 to 15 years. Age at onset ranged from 2 to 81 years old. Growth curve analysis using linear mixed effects regression were used to examine possible outcomes controlling for gender, age of onset and all interactions. Results: Results show that total motor score, symbol digit, Stroop colour naming and general functioning have more rapid progression with earlier age of onset. Conclusion: Comparison curves will be shown for various subgroups with onset ages of 18, 30, 45, 60 and 80 demonstrating varying rates of progression. Implications for clinical trial design will be addressed.